KARAKTERISTIK PENGERINGAN KULIT MANGGIS DENGAN ALAT PENGERING HIBRID TIPE RAK - Rofandi Hartanto; . Warji; Wahyu Rusdiyanto (Faculty of Agricultural Technology, University of Jember, 2011)
Number of constraints in drying of mangosteen peel came as problem in handling of the product. The hybrid drying system was chosen as an alternative to dry the mangosteen peel. The treatments performed in this research were: the rack dryer hybrid where sunlight, electric, and combination of sunlight and electric source, and as a comparison were used the para-para dryer. Combination of sunlight and electric source has the highest temperature that was 48.5 C deg. using electric source was 38.1 C deg., whereas using sunlight source was 39.6 C deg. and using para-para dryer was 33.6 C deg. Drying with combination of sunlight and electric source was the most rapid in moisture evaporation. While as a comparison was used the para-para dryer, that was the slowest one. Drying efficiency using sunlight source was 29.6%, while the drying efficiency using electric source was 51.5%, and the combination of sunlight and electric source was 28.7%. It was concluded that the hybrid dryer could be used as an alternative to dry mangosteen peel.Keywords: mangosteen peel, drying energy source, drying efficiency